2018
DOI: 10.1590/s1678-86212018000200241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cement type and water content on the fresh state properties of ready mix mortar

Abstract: The main characteristic of ready mix mortar is to remain workable for up to 72hours after mixing. This greater duration of workability is obtained by use of hydration stabilizing admixtures and air-entrained admixtures. Thus, the behavior of this mortar depends on the compatibility between Portland cement and these two admixtures. Within this context, the objective of this article is to evaluate the influence of Portland cement type and water content on the properties of ready mix mortars in fresh state. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
2
6
0
6
Order By: Relevance
“…The workability loss (i.e. increases in the consistency and plasticity values) over time observed for the 6 MPa mortar is in line with the results reported by Casali et al (2018), who found reductions in the flow table test values over time for ready-mixed mortars produced with different types of Portland cement. The authors justified this behaviour by a possible start in the cement hydration reactions.…”
Section: Ready-mixed Mortarsupporting
confidence: 91%
See 2 more Smart Citations
“…The workability loss (i.e. increases in the consistency and plasticity values) over time observed for the 6 MPa mortar is in line with the results reported by Casali et al (2018), who found reductions in the flow table test values over time for ready-mixed mortars produced with different types of Portland cement. The authors justified this behaviour by a possible start in the cement hydration reactions.…”
Section: Ready-mixed Mortarsupporting
confidence: 91%
“…In addition, the compaction process performed during the slump test may remove part of the entrained air of the mixtures, while the Gtec test is performed in a mortar sample that is practically undisturbed, which is closer to a real condition. Casali et al (2018) also reported the limitation of some empirical tests on the evaluation of fresh state properties of mortars. The authors evaluated the influence of the cement type and storage time on the fresh properties of ready-mixed mortars.…”
Section: Ready-mixed Mortarmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the analyzed cases, an increase in the amount of water caused a decrease in air content, while a decrease in the amount of water resulted in its increase. A similar effect was observed by Cesali et al [74]. On the basis of both research data, it could be concluded that it might be possible that it was due to differences in the volume of porous mortar occupied by water.…”
Section: Impact Of Inaccuracies In Dosing Watersupporting
confidence: 85%
“…A combinação dos aditivos incorporador de ar e estabilizador de hidratação, bem como seus efeitos sobre a argamassa fresca e endurecida, vem sendo tema frequente de estudos. A aplicação e a dosagem desses aditivos, cada vez mais, requerem uma análise conjunta (ANTONIAZZI, 2019), considerando as bases químicas empregadas (CHEUNG et al, 2011;GUINDANI, 2018), o tipo de cimento (CASALI et al, 2018), a granulometria do agregado (BAUER; OLIVEIRA, 2017) e as características da mistura (ROMANO et al, 2009;FUKUI et al, 2018), entre outros fatores. Dessa forma, os estudos deveriam associar teores mais baixos de aditivos com fatores que potencializassem seus efeitos, buscando explorar sua máxima eficiência sem comprometer as propriedades da argamassa.…”
Section: Introductionunclassified